Fc gamma Receptor IIa‐H131R Polymorphism and Malaria Susceptibility in Sympatric Ethnic Groups, Fulani and Dogon of Mali. (January 2014) - Maiga, B.; Dolo, A.; Touré, O.; Dara, V.; Tapily, A.; Campino, S.; Sepulveda, N.; Corran, P.; Rockett, K.; Clark, T. G.; Troye Blomberg, M.; Doumbo, O. K.
Abstract It has been previously shown that there are some interethnic differences in susceptibility to malaria between two sympatric ethnic groups of Mali, the Fulani and the Dogon. The lower susceptibility to Plasmodium falciparum malaria seen in the Fulani has not been fully explained by genetic polymorphisms previously known to be associated with malaria resistance, including haemoglobin S (HbS), haemoglobin C (HbC), alpha‐thalassaemia and glucose‐6‐phosphate dehydrogenase (G6PD) deficiency. Given the observed differences in the distribution of FcγRIIa allotypes among different ethnic groups and with malaria susceptibility that have been reported, we analysed the rs1801274‐R131H polymorphism in the FcγRIIa gene in a study of Dogon and Fulani in Mali (n = 939). We confirm that the Fulani have less parasite densities, less parasite prevalence, more spleen enlargement and higher levels of total IgG antibodies (anti‐CSP, anti‐AMA1, anti‐MSP1 and anti‐MSP2) and more total IgE (P < 0.05) compared with the Dogon ethnic group. Furthermore, the Fulani exhibit higher frequencies of the blood group O (56.5%) compared with the Dogon (43.5%) (P < 0.001). With regard to the FcγRIIa polymorphism and allele frequency, the Fulani group have a higher frequency of the H allele (Fulani 0.474, Dogon 0.341, P < 0.0001), which was associated with greater total IgE production (P = 0.004). Our findings show that the FcγRIIa polymorphism might have an implication in the relative protection seen in the Fulani tribe, with confirmatory studies required in other malaria endemic settings.